Insulin-derived amyloidosis - Gupta, Yashdeep (Indian J Endocrinol Metab, 2015)
Amyloidosis is the term for diseases caused by the extracellular deposition of insoluble polymeric protein fibrils in tissues and organs. Insulin-derived amyloidosis is a rare, yet significant complication of insulin therapy. Insulin-derived amyloidosis at injection site can cause poor glycemic control and increased insulin dose requirements because of the impairment in insulin absorption, which reverse on change of injection site and/or excision of the mass. This entity should be considered and assessed by histopathology and immunohistochemistry, in patients with firm/hard local site reactions, which do not regress after cessation of insulin injection at the affected site. Search strategy: PubMed was searched with terms “insulin amyloidosis”. Full text of articles available in English was reviewed. Relevant cross references were also reviewed. Last search was made on October 15, 2014.